PERSEPSI PETANI DAN PENYULUH PERTANIAN LAPANG (PPL) TENTANG REVITALISASI PERTANIAN PADA ASPEK PENATAAN KELEMBAGAAN DI KABUPATEN SRAGEN - Bekti Wahyu Utami; Dwiningtyas Padmaningrum; Hanifah Ihsaniyati (AGRITEXTS: Journal of Agricultural Extension, 2007)
To previous research entitling "Penataan Kelembagan Penyuluhan Pertanian Dalam Rangka Revitalisasi Penyuluhan Pertanian di Kabupaten Sragen " the aimed of rhis research circumstansial congeniality about settlement of extension institute in Sragen Regency. The research result showed in the effort revitality extension agriculture in Sragen Regency have formed the "house self' to field extension workers namely with "Badan Pelaksana Penyuluhan (BAPELUH)." In other side, so far perception of field extension workers and farmer toward effort revitality institute is positif. According to them, with the existance of this program, field extension workers more paid attention. Though some among farmer don't know the name of extension revitality instirute but farmer assess the condition of farmers extension workers in now more motivated, active and proactive and progressively entangle the farmer partisipatively in decision making.